Colchicine Poisoning Cases in a Pediatric Intensive Care Unit: A Twenty-Year Study. Issue 10 (26th October 2022) - Süzen-Orhan, Eda; Botan, Edin; Gün, Emrah; Özen, Hasan; Gurbanov, Anar; Balaban, Burak; Kahveci, Fevzi; Vatansever, Göksel; Tekin, Deniz; Kendirli, Tanıl
Abstract : Objectives: Colchicine intoxication is rare but potentially fatal. The toxic dose of colchicine is not well established; it has been reported that major toxicity starts after doses of 0.5 mg/kg. We aimed to evaluate the demographic, clinical aspects, treatments, and outcome of colchicine toxicity cases in the pediatric intensive care unit (PICU). Methods: We collected the data of patients aged between 0 and 18 years, admitted to Ankara University Faculty of Medicine PICU for colchicine poisoning (n = 22), from October 1999 to January 2020, retrospectively. Data extracted from the cases included age, sex, chronic condition, time between intake of drug and admission to PICU, source of drug, amount of drug ingested, other drug intake, symptoms, clinical findings, cardiac involvement, laboratory results, time of stay in PICU, treatment, and outcome. Results: Patients' age ranged from 7 months to 17 years. Median age was 86 months. The most common symptom at time of admission was vomiting, occurring in 13 (59%) of the patients. Two of the patients presented with change in mental status. Time between taking medication and applying to the hospital ranged from half an hour to 4 days. Medication intake of 3 of 22 patients was more than 0.5 mg/kg. One patient whose parents' best estimate of dose ingested was 0.48 mg/kg died because of the development of multiorgan failure. One patient who ingested 0.4 mg/kg of colchicine underwent plasma exchange and recovered without any complications. Conclusions: Colchicine poisoning has a high risk of mortality, and death can be seen in doses less than a single acute dose of 0.5 mg/kg. These patients need close monitoring because there is always a risk of them to require aggressive support. Prognosis is poor in patients who have rapidly developing hemodynamic failure.